2001
DOI: 10.1016/s0022-2275(20)31643-6
|View full text |Cite
|
Sign up to set email alerts
|

Sterols in blood of normal and Smith-Lemli-Opitz subjects

Abstract: Smith-Lemli-Opitz syndrome (SLOS) is a hereditary disorder in which a defective gene encoding 7-dehydrocholesterol reductase causes the accumulation of noncholesterol sterols, such as 7-and 8-dehydrocholesterol. Using rigorous analytical methods in conjunction with a large collection of authentic standards, we unequivocally identified numerous noncholesterol sterols in 6 normal and 17 SLOS blood samples. Plasma or erythrocytes were saponified under oxygen-free conditions, followed by multiple chromatographic s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 55 publications
2
16
0
Order By: Relevance
“…They are not affected by everyday diet; however, after institution of strongly cholesterol-enriched diet for several months, effects on sterol metabolism have been shown. It should be noted that variation in sterol levels stems from differences in genotype, age, diet, rate of growth, and other factors (Ruan et al, 2001). For example, in the SLO syndrome, the elevation of 7-DHC ranged from 100-fold in mild cases to about 10,000-fold in a severely affected subject (Ruan et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They are not affected by everyday diet; however, after institution of strongly cholesterol-enriched diet for several months, effects on sterol metabolism have been shown. It should be noted that variation in sterol levels stems from differences in genotype, age, diet, rate of growth, and other factors (Ruan et al, 2001). For example, in the SLO syndrome, the elevation of 7-DHC ranged from 100-fold in mild cases to about 10,000-fold in a severely affected subject (Ruan et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that variation in sterol levels stems from differences in genotype, age, diet, rate of growth, and other factors (Ruan et al, 2001). For example, in the SLO syndrome, the elevation of 7-DHC ranged from 100-fold in mild cases to about 10,000-fold in a severely affected subject (Ruan et al, 2001). In their study on 84 patients with SLO syndrome, Witsch-Baumgartner et al (2000) found also a positive correlation between clinical severity and elevated relative 7-DHC concentration.…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of product compositions was done by GC, by 1 H NMR, by UV-Vis, by fluorescence, by MS, and by GC/ MS. We used a Bruker/Varian CP-3800 gas chromatograph equipped with an electronic integrator for CTL and for stilbene actinometry. Semi-preparative HPLC was performed using a Beckman Coulter System Gold 125 solvent module with a System Gold 168 detector.…”
Section: Methodsmentioning
confidence: 99%
“…The natural products cholesta-5,7,9(11)-trien-3β-ol (CTL) and its close relative 9(11)-dehydroergosterol (DHE) differ from provitamin D 3 (Pro) and ergosterol (E), respectively, by the additional C 9 -C 11 double bond [1][2][3][4][5][6]. The cholestane skeleton lends rigidity to their embedded conjugated triene moieties increasing S 1 lifetimes by diminishing torsional relaxation, thereby rendering them fluorescent [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation